Pengaplikasian Turbin Angin dan Generator Sebagai Sumber Pengisian Baterai pada Mobil Listrik - Sakti, Amario Prananda; Pambudi, Nugroho Agung (Jujurnal Publisher, 2025)
Electrical energy is the main need in modern life, especially in the development of electric vehicle technology. However, limited power resources and charging efficiency are challenges in the implementation of electric cars. Indonesia has great potential in the use of renewable energy, one of which is wind energy. This study aims to find out how the Wind Power Plant system and generator work as a source of battery charging in electric cars.This study uses an experimental method with a quantitative analysis technique approach. This study uses variables that are measured including wind speed, voltage, current, and electrical power generated by the generator at various vehicle speeds. The test was carried out in two different locations, namely the Solo-Sragen Ring Road and the Karanganyar-Solo Toll Road, to compare the performance of the system in varying environmental conditions.The test results show that the speed of the vehicle is directly proportional to the electrical power produced. At a vehicle speed of 20 km/h, the generator starts to produce 2.6 Watts of electrical power, while at a speed of 100 km/h, the power produced reaches 9.6 Watts. However, fluctuations in current and voltage values occur due to variations in wind speed and vehicle aerodynamic resistance. However, the electrical voltage generated has met the minimum standard of battery charging, which is 12–13.8 Volts